PENGARUH LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA: (Studi Kasus Pada Karyawan KSP AMAJ Kota Magelang) - Nabila Restu Rahmanda; Dian Marlina Verawati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the effect of the work environment on the morale of the employees of KSP Artha Mitra Abadi Jaya, Magelang City. The method used in this research is quantitative with data collection by questionnaire. The population and samples used in this study were all employees at KSP AMAJ Magelang City, totaling 30 people. Determination of the sample in this study is using the census method. The data in this study were obtained by using the questionnaire method. In managing the data, the researcher used a simple linear regression technique using SPSS 24 software. According to the findings, it is revealed that the work environment (X) has a significant influence on work morale (Y) employees at KSP Artha Mitra Abadi Jaya, Magelang City.